Pengaruh Padat Tebar terhadap Konsumsi Oksigen dan Respons Stres Ikan Cupang Alam (Betta imbellis) - Shofihar Sinansari; Vitas Atmadi Prakoso; Erma Primanita Hayuningtyas; Bambang Priadi; Sri Sundari; Eni Kusrini, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Effect of Stocking Density on Oxygen Consumption and Stress Response in Crescent Betta (Betta imbellis). Stocking density is one of the determinant parameters for fish growth optimization in aquaculture systems due to its relationship with fish metabolism. Information about the impact of different stocking densities on crescent betta (Betta imbellis) metabolism was not available yet. This study was aimed to analyze the effect of stocking density on oxygen consumption, critical oxygen level, and stress responses in crescent betta.The study was carried out under three different stocking density treatments: 5, 10, and 15 fish/L with three replications using 2.74 ± 0.23 cm total length and 0.22 ± 0.05 g body weight tested fishes.The parameters observed were oxygen consumption, ventilation rate, blood glucose level, cortisol, and critical oxygen level. The result showed that the highest oxygen consumption was found at 5 fish/L stocking density treatment (3.01 ± 0.28 mg O2/g/h), which was significantly different from 10 fish/L (1.01 ± 0.21 mg O2/g/h) and 15 fish/L (0.92 ± 0.08 mg O2/g/h) stocking density treatments. Oxygen consumptions under hypoxic condition was not significantly different compared to normoxic condition.The ventilation rate tends to increase significantly along with the increasing of stocking densities. Critical oxygen levels were not significantly different among the treatments,with the value of 3.31 ± 0.65 mg/L, 3.14 ± 0.29 mg/L, and 2.83 ± 0.19 mg/L for stocking density of 5, 10, and 15 fish/L, respectively. The blood glucose level at 15 fish/L stocking density was significantly higher than others, whereas the cortisol levels was not significantly different among the treatments. The results of this study provided information that the increasing stocking density of cressent betta will decrease their metabolism activity and increase ventilation rate. However, the increase of ventilation rate was negatively correlated with oxygen consumption per breath at higher stocking densities due to decrease in fish activity; and higher stocking densities will decrease oxygen consumption. Based on the results, it can be concluded that the ideal stocking density for crescent betta is 5 fish/L. The increasing of stocking density will decrease oxygen consumption rates and increase the stress level of crescent betta.